The Impact of Artificial Intelligence Integration in Kazakhstan's Manufacturing Sector - Kakimov Bakhtiyar Kuanyshuly (Scientific Research and Experimental Development, 2024)
The integration of Artificial Intelligence (AI) in the manufacturing sector marks a critical step forward in Kazakhstan's industrial and economic evolution. This paper explores the impact, extent, and future prospects of AI adoption within Kazakhstan's manufacturing landscape, underpinned by initiatives like "Digital Kazakhstan." The study highlights the potential for efficiency gains, economic growth, and enhanced competitiveness through strategic AI integration, aligning with national goals for economic diversification and innovation. It addresses the challenges faced, including the need for substantial technological investments, workforce adaptation to new technologies, and the imperative for educational and policy reforms to support this transition. The findings suggest that while integrating AI into manufacturing processes promises significant benefits such as improved productivity, economic diversification, and a reduced environmental footprint, realizing these benefits demands a coordinated approach involving substantial investment in technology infrastructure, an overhaul of the educational system to produce a workforce proficient in AI and related technologies, and robust policy reforms to foster an innovation-friendly environment. The paper concludes that despite the complexities involved, the rewards of industrial modernization, sustainable development, and economic resilience are profound, positioning Kazakhstan as a potential leader in technological innovation and digital transformation within the manufacturing sector.